2009
DOI: 10.1021/la901696t
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Energy Dissipation of Electrolytes in Nanopores

Abstract: When a nonwetting fluid is forced to infiltrate a hydrophobic nanoporous solid, the external mechanical work is partially dissipated into thermal energy and partially converted to the liquid-solid interface energy to increase its enthalpy, resulting in a system with a superior energy absorption performance. To clarify the energy dissipation and conversion mechanisms, experimental infiltration and defiltration tests of liquid/ion solutions into nanopores of a hydrophobic ZSM-5 zeolite were conducted. The charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Indeed, it has been shown that having hydrophobic properties along with nanoporous structure induces a special interaction between hydrogels chains and water composing the hydrogel that can highly increase the dissipation (Surani et al, 2005;Zhao et al, 2009;Kong and Qiao, 2005). For such a material immersed in water or in a nonwetting liquid, previous published studies showed that when external mechanical pressure exceeds a critical threshold, the liquid can be forced to defiltrate or infiltrated the hydrophobic nanopores (Surani et al, 2005;Zhao et al, 2009;Kong and Qiao, 2005). In other words, there will be a defiltration (drainage) and infiltration pressure during loading and unloading that increase interfacial energy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, it has been shown that having hydrophobic properties along with nanoporous structure induces a special interaction between hydrogels chains and water composing the hydrogel that can highly increase the dissipation (Surani et al, 2005;Zhao et al, 2009;Kong and Qiao, 2005). For such a material immersed in water or in a nonwetting liquid, previous published studies showed that when external mechanical pressure exceeds a critical threshold, the liquid can be forced to defiltrate or infiltrated the hydrophobic nanopores (Surani et al, 2005;Zhao et al, 2009;Kong and Qiao, 2005). In other words, there will be a defiltration (drainage) and infiltration pressure during loading and unloading that increase interfacial energy.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, there will be a defiltration (drainage) and infiltration pressure during loading and unloading that increase interfacial energy. In this situation, the forced in and out motion of the liquid molecules will increase the energy dissipation via friction-like interaction between solid and liquid phases (Surani et al, 2005;Zhao et al, 2009;Kong and Qiao, 2005). Beside the two specific properties related to solid-fluid interactions, the high dissipation of HEMA-EGDMA hydrogels could also be related to the sub-molecular structure of these hydrogels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of hydrophilic nature of HEMA monomers, it is postulated that PHEMA hydrogel has, in addition to its covalently linked network structure, a secondary structure stabilized by hydrophobic bonding [30]. It has been showed that for a hydrophobic porous material, because of an defiltration (drainage) and infiltration pressure, force is required to move liquid in and out of the material pores [31]. Without mechanical loading the structure is reluctant to exchange fluid and facilitate the payload release.…”
Section: Discussionmentioning
confidence: 99%